2017
DOI: 10.1002/jor.23617
|View full text |Cite
|
Sign up to set email alerts
|

Novel porcine experimental model of severe progressive thoracic scoliosis with compensatory curves induced by interpedicular bent rigid temporary tethering

Abstract: The tether release model will be used to evaluate corrective non-fusion technologies in future investigations. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:174-182, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In that study we similarly found rotation, but limited to 9 degrees and only minimal coronal deformation of 6 degrees, which cannot be regarded as a suitable model for scoliosis [7]. In the current mini-pig model, including a contralateral tether, the mean coronal curves were 19 degrees, which we consider as relevant although smaller than other studies where more aggressive techniques were used in faster growing animals [14,15,[30][31][32]. However, more important than coronal curve size is that the curves are consistent, the spine remains mobile and includes all 3D characteristics, including axial rotation and anterior lengthening in the disk, of idiopathic scoliosis [7].…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…In that study we similarly found rotation, but limited to 9 degrees and only minimal coronal deformation of 6 degrees, which cannot be regarded as a suitable model for scoliosis [7]. In the current mini-pig model, including a contralateral tether, the mean coronal curves were 19 degrees, which we consider as relevant although smaller than other studies where more aggressive techniques were used in faster growing animals [14,15,[30][31][32]. However, more important than coronal curve size is that the curves are consistent, the spine remains mobile and includes all 3D characteristics, including axial rotation and anterior lengthening in the disk, of idiopathic scoliosis [7].…”
Section: Discussionmentioning
confidence: 42%
“…A surrogate method is to investigate the ability of the individual or combined components to induce and subsequently reduce scoliosis-like deformities in a growing animal model. Rigorous induction methods like rib fusions or unilateral rods that fuse the spine are less optimal from that perspective, as the deformity is often very rigid, uniplanar, unpredictable, and thus behaves more like a congenital scoliosis [9,14,15]. A more relevant induction method is through unilateral flexible posterior tethering [15,16].…”
Section: Introductionmentioning
confidence: 99%